Sou capoeira: a construção de um novo fazer-se capoeirista analisado por meio das gravações de lps entre as décadas de 1980 a 1990 - Belfante, Diego Bezerra (2018)
Between the 1980s and 1990s, changes occurred in the experiences of capoeiristas. Such changes can be witnessed in capoeira songs. Through this fundamental element for the practice of capoeira we can analyze how this group constitute own versions for the narratives of the history of Brazil and capoeira. During the period covered by our clipping, it was possible to observe the growth of capoeira that occurred concomitantly with a deep social and cultural transformation in Brazilian society. These changes reverberated in capoeira, thus creating new practices and visions about what it is to be a capoeirista. What made her change the way the capoeiristas relate to each other and to the rest of society. From this perspective this research seeks to study the changes in the making of the capoeiristas between the decades that our clipping covers. Using as a source the recordings of LPs undertaken individually by masters or collectively by groups of capoeira. Therefore, in our analysis we noticed that, in the songs recorded in LPs in this period, two major themes gain strength and stand out from the others. It is tradition and freedom. Contrary to what one might think at first, these themes combine as complementary. The narrative constructions of the songs begin to use freedom and tradition as the cornerstones of the discourse that capoeira produces about itself. Such construction is closely linked with the new conformation of the capoeirístico field that has taken place from the process that we investigated. Therefore, we defend that from the process of expansion of capoeira by Brazil and abroad together with the emergence of a new scenario for social and cultural movements from the end of the 1970s deeply alter capoeira in order to make this practice linked to a ideal of freedom that tradition serves as legitimizer.